Tradisi Adat Kalomba: Kajian Makna dan Nilai Budaya Pada Masyarakat Desa Bonto Biraeng Kabupaten Bulukumba - Muslimin, Ainun syafitri; Kurniawan, Andi; Vebriani, Nunu; Hikmah, Nurul (Titian: Jurnal Ilmu Humaniora, 2021)
Abstract The purpose of this study is to determine the process of the Kalomba tradition, meanings and values contained in the traditional process of the Kalomba tradition. Kalomba tradition is a tradition carried out by the Kajang Tribe aimed at the age of children to avoid skin diseases. The method used in this research is qualitative with an ethnographic approach. Determination of informants using purposive sampling and snowball sampling. Data collection was carried out through interviews, observation and documentation as well as data analysis consisting of data collection, data reduction, data presentation and deduction. The results of this study revealed that the Kalomba tradition began during the Karaeng Padulu Soreang period whose marriage was not approved and then a child was born. When parents who do not agree to meet must fulfill these terms and conditions, this is known as Kalomba. The traditional Kalomba tradition is carried out based on stages starting from the ma’jenne procession, burning incense and lighting candles, reading prayers, waving incense smoke, tompong procession, baccing children procession, paddingi-dingi stage, massolo (giving money to children) and the event ends the setting of kampalo on eating together by family and relatives.The meaning of the Kalomba tradition is as medicine and safety to avoid skin diseases and as a thanks giving from parents to children. The Kalomba tradition reveals the value of helping each other and togetherness, establishing friendship and responsibility.